Genetics of lodging resistance related traits in bread wheat (Triticum aestivum L.) - Muazzam, Sana; Khan, Abdus Salam; Ali, Zulfiqar; Khan, Sultan Habibullah (Bangladesh Journal of Botany, 2020)
To evaluate the genetic background of lodging traits, six populations of two wheat crosses were sown under different nitrogen levels by using split plot design. Generation mean analysis was used to estimate the gene action for lodging related traits. Results showed genetic variability and significant differences for all traits. Allelic and non-allelic gene actions were operative for different traits with different magnitude under both normal and lodging condition. Duplicate types of espistasis were observed for grain yield per plant, 1000- kernel weight, number of grains per spike and number of tillers. The stem diameter, height of basal nodes and basal inter-nodal distance depicted the additive, additive × dominance and dominance gene action. The aforementioned results showed that plant height, stem diameter, height of basal nodes and basal internodal distance were more prone traits for lodging and selection should be practiced in later generations with increasing homozygosity.